2020
DOI: 10.21037/tcr-19-2349
|View full text |Cite
|
Sign up to set email alerts
|

Treatment and prognosis of primary malignant melanoma of the esophagus

Abstract: Background Primary malignant melanoma of the esophagus (PMME) is rare with high malignancy and poor prognosis. The aim of this study was to investigate the relationship between prognosis and clinicopathological characteristics of this disease. Methods A total of 9 patients with PMME were treated in Zhejiang Cancer Hospital between 2009 and 2019 retrospectively. According to 8th edition AJCC/UICC staging of cancers of the esophagus and esophagogastric junction, none of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Melanoma is one of the most harmful skin cancers, usually originating from ultraviolet exposure from sunshine or tanning beds (1,2). In recent years, more than 150,000 people worldwide have been diagnosed with melanoma cancer annually, of which 30% of cases have been invasive and dangerous (3,4). Therefore, early diagnosis and suitable treatment of melanoma is critical and urgently required.…”
Section: Introductionmentioning
confidence: 99%
“…Melanoma is one of the most harmful skin cancers, usually originating from ultraviolet exposure from sunshine or tanning beds (1,2). In recent years, more than 150,000 people worldwide have been diagnosed with melanoma cancer annually, of which 30% of cases have been invasive and dangerous (3,4). Therefore, early diagnosis and suitable treatment of melanoma is critical and urgently required.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, these authors renewed the need to employ techniques such as massive gene sequencing to be able to search for biomarkers capable of predicting the response of PMME to anti-PD1 immunocheckpoint inhibitors. After another 38 cases of PMME [ 274 , 277 , 278 , 279 , 280 , 281 , 282 , 283 , 284 , 285 , 286 , 287 , 288 , 289 ], Endo F. et al [ 290 ] reported a case of a 70-year-old man who complained of dysphagia due to the presence of a polypoid lesion in the lower thoracic esophagus. Although the histopathological examination had provided the diagnosis of esophageal squamous carcinoma at first, with subsequent pT3N1M0 staging and clinical stage III, a histological re-evaluation after radical esophagectomy revealed the presence of atypical melanocyte cells positive for S-100 protein, Melan-A and HMB-45, and, therefore, PMME was diagnosed.…”
Section: Discussionmentioning
confidence: 99%
“…PMME is a rare and highly aggressive tumor with a high recurrence rate and poor prognosis. PMME accounts for 0.1–0.2% of all malignant esophageal tumors ( 68–70 ). The median age at diagnosis is 60.4 years, which is younger than that for esophageal squamous cell carcinoma ( 71 ).…”
Section: Primary Malignant Melanoma Of the Esophagusmentioning
confidence: 99%
“…PMME originates in the lower to middle esophagus in approximately 90% of cases ( 71 ). It has been presumed that melanoblasts migrate from the neural crest to various sites, such as the epidermis, oral cavity and uvea, where the primary malignant melanoma arises ( 68 , 69 , 74 , 75 ). The esophagus normally does not contain melanoblasts, so abnormal migration of esophageal melanocytes may explain the occurrence of PMME ( 59 , 75 ).…”
Section: Primary Malignant Melanoma Of the Esophagusmentioning
confidence: 99%
See 1 more Smart Citation